Learning from past collaborative experiences: setting a pathway for natural sciences and engineering researchers to support Indigenous-driven aims - Heather L. Greenwood; Alex Choi; Roxanna Dehghan; Becky Big Canoe; Kristian Dubrawski; Emilee Gilpin; Marie-Chantal Ross; Eric Wilson; Amy M. Bilton (FACETS)
In efforts to contribute towards reconciliation, some researchers have shown increased interest in collaborative work with Indigenous Peoples. However, those in technical fields, such as the natural sciences and engineering, are not traditionally trained in how to carry out Indigenous-driven research. This study learned from the successes and challenges of past technical research collaborations to better understand how these researchers can act as stronger allies. Qualitative interviews were carried out with five members of Indigenous communities and 35 researchers. The results showed diverse experiences and the need for more collaborative frameworks and supportive institutional environments within the natural sciences and engineering. Findings highlighted the wide range of issues to be considered in such work, grouped into (1) assessing personal preparation and mindset; (2) building and maintaining relationships; (3) community-aligned benefit; (4) practical and financial considerations; and (5) knowledge sharing and communication. In addition, participants identified institutional-level factors that could help (e.g., mentorship) or hinder (e.g., current recognition structures in many technical fields) efforts to carry out Indigenous-driven technical research. These results may stimulate and contribute to necessary work in the natural sciences and engineering on processes for equitable and thoughtful engagement with members of Indigenous communities to support Indigenous-driven research.